2000
DOI: 10.1073/pnas.150227197
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of resistance to experimental infection with virulentMycobacterium tuberculosis

Abstract: Over 2 billion people are estimated to be infected with virulent Mycobacterium tuberculosis, yet fewer than 10% progress to clinical tuberculosis within their lifetime. Twin studies and variations in the outcome of tuberculosis infection after exposure to similar environmental risks suggest genetic heterogeneity among individuals in their susceptibility to disease. In a mouse model of tuberculosis, we have established that resistance and susceptibility to virulent M. tuberculosis is a complex genetic trait. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
228
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 292 publications
(233 citation statements)
references
References 46 publications
5
228
0
Order By: Relevance
“…Now the future of mouse genetics in the study of host resistance to Salmonella and other infections is moving toward the identification of inbred mouse strains that show a complex mode of inheritance to specific pathogens for QTL gene identification. 19,20,[153][154][155][156][157][158][159][160] Dissection of the complex host response to Salmonella infection combined with the complete mouse genome sequence will contribute further to our understanding of the genetic control of host immunity.…”
Section: Resultsmentioning
confidence: 99%
“…Now the future of mouse genetics in the study of host resistance to Salmonella and other infections is moving toward the identification of inbred mouse strains that show a complex mode of inheritance to specific pathogens for QTL gene identification. 19,20,[153][154][155][156][157][158][159][160] Dissection of the complex host response to Salmonella infection combined with the complete mouse genome sequence will contribute further to our understanding of the genetic control of host immunity.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, extensive in vitro data implicating TLR2 in the recognition of mycobacterial lipoarabinomannan, 31 a soluble tuberculosis factor, 22 whole Mycobacterium avium, 71 and Mycobacterium tuberculosis 72,73 strongly suggest that one or more TLRs participate in mycobacterial host defense. Published genetic analyses of experimental mycobacterial infection among different strains of inbred mice have identified significant QTL for tuberculosis susceptibility (sst1) on mouse chromosome 1 74 as well as resistance (Trl1-3) on mouse chromosomes 1, 3, and 7. 75 TLR5 is located on chromosome 1 but is unlikely to be a candidate gene for either the susceptibility or resistance phenotypes since it maps distal to both candidate intervals.…”
Section: Mycobacterial Infectionmentioning
confidence: 99%
“…We have showed that in addition to DNA-damaging reactive oxygen and nitrogen species, the MTB-infected macrophages produce a most potent member of the epidermal growth factor family epiregulin, which may serve as a paracrine growth factor at the initial steps of tumorigenesis. We also identified a powerful genetic modifier of MTB-induced lung tumorigenesis in our model: the genetic locus sst1 (Kramnik et al, 2000), which specifically controls tissue damage and TB progression in the lungs.…”
Section: Introductionmentioning
confidence: 99%